Condições socioeconômicas na infância e rigidez arterial na vida adulta segundo raça/cor. Estudo longitudinal de saúde do adulto (ELSA-Brasil) - Débora Moraes Coelho (2018)
INTRODUCTION: Socioeconomic disadvantages in childhood are associated with higher cardiovascular risk (CVD) in adult life. In the same way, individuals of black color have worse markers of CVD. However, little is known about the effect of these two disadvantages on arterial stiffness, an important subclinical marker of cardiovascular risk (CVD). OBJECTIVES: We investigated the association between social and nutritional adversities in childhood and increased arterial stiffness in adulthood, according to race/skin color. METHODS: Participed 13,365 individuals from the baseline (2008-2010) of the ELSABrazil, aged between 34 and 75 years, without a diagnosis of CVD. Arterial stiffness was measured by carotid-femoral pulse wave velocity (cfPWV) in m/s; the socioeconomic condition in childhood by maternal schooling and birth weight, and race/color was selfreported. Covariates considered were: age, sex, participant schooling, physical activity, smoking, weight, height, mean arterial pressure, heart rate, diabetes and use of antihypertensive drugs. Linear regression models were used to analyze the relationship between childhood adversity and cfPWV in adulthood. RESULTS: Maternal schooling was associated with cfPWV in adult life in all race/color subgroups, but lost significance after adjusting for participant schooling among Whites. In Browns and Blacks, lower maternal schooling was associated with higher cfPWV in adult life independent of current schooling and behavioral and clinical variables. In Blacks, the children of women who never attended school showed an increase of 0.44m/s (95% CI: 0.18;0.70) in the mean of cfPWV in relation to those of mothers who had completed high school or higher. In Browns, this increase was 0.18m/s (95% CI: 0.01;0.34). On the other hand, the association between low birth weight and higher cfPWV was found only among Whites, and Whites who were low birth weight showed an increase of 0.17m/s (95% CI: 0.00;0.34) in the mean of cfPWV in relation to those who were born with adequate weight (≥ 2.5 kg and ≤ 4.0 kg). CONCLUSION: Our results suggest that exposure to social and nutritional adversity in childhood, as measured by maternal schooling, was associated with higher PWV among browns and blacks, which partially explains the disproportionate burden of morbidity and mortality due to cardiovascular diseases in this group. The fact that the association between birth weight and arterial stiffness was only present in Whites may have reflected a survival bias.